High performance controller for drying processes - doi: 10.4025/actascitechnol.v35i2.14775 - Boeri, Camila Nicola; Silva, Fernando Neto da; Ferreira, Jorge (Acta Scientiarum. Technology, 2012)
This paper proposes a high performance nonlinear fuzzy multi-input-multi-output controller for a drying control process. The highly nonlinear characteristics of drying processes make classical control theory unable to provide the same performance results as it does in more well behaved systems. Advanced control strategies may be used to design temperature, relative humidity and air velocity nonlinear tracking controllers to overcome its highly non-linear dynamics over the whole drying operating conditions. Open-loop experiments were carried out to collect experienced-based knowledge of the process. PID and Fuzzy logic (FLC) real-time-based controllers were designed to perform food drying tests and compared without controllers´ retuning. Absolute errors reached by FLC-based controller were 3.71 and 3.93 times lower than PID for temperature and relative humidity, respectively. Â